Efficient and robust coatings using poly(2‐methyl‐2‐oxazoline) and its copolymers for marine and bacterial fouling prevention. Issue 2 (7th October 2015) - He, Tao; Jańczewski, Dominik; Jana, Satyasankar; Parthiban, Anbanandam; Guo, Shifeng; Zhu, Xiaoying; Lee, Serina Siew‐Chen; Parra‐Velandia, Fernando Jose; Teo, Serena Lay‐Ming; Vancso, G. Julius
ABSTRACT: Molecular design, fabrication, and properties of thin‐film coatings based on poly(2‐methyl‐2‐oxazoline) (PMOX) and its copolymers were investigated to tackle problem of marine and bacterial fouling prevention. The ultraviolet crosslinkable macromonomer poly(2‐methyl‐2‐oxazoline) dimethylacrylate was synthesized by cationic ring‐opening polymerization in a microwave reactor initiated by 1, 4‐dibromobutane. In order to study the charge effect of the PMOX coatings on the adhesion of fouling organisms, PMOX surfaces with negative, neutral, and positive ζ‐potential values were prepared by copolymerization with the positively charged monomer [2‐(methacryloyloxy)‐ethyl]trimethylammonium chloride. The coatings were stable in sea water for at least 1 month without significant reduction in the film thickness. The marine antifouling activity was evaluated against barnacle cyprids Amphibalanus amphitrite and algae Amphora coffeaeformis . Results showed that PMOX coatings provide effective reduction of the settlement regardless of the molar mass and surface charge of the polymer. Bacterial adhesion test showed that PMOX coatings effectively reduce Staphylococcus aureus and Escherichia coli adhesion. Owing to its good stability and antifouling activity PMOX has a great potential as antifouling coating for marine antifouling applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 275–283 Abstract : Thin‐film coatings based on PMOX and its copolymers with negative, neutral, and positive ζ‐potential were investigated to tackle the problem of marine and bacterial fouling prevention. The coatings were stable in sea water for at least 1 month without significant reduction in the film thickness. Performance tests showed that PMOX coatings effectively reduced bacterial Staphylococcus aureus and Escherichia coli adhesion and possessed marine antifouling activity against barnacle cyprids Amphibalanus amphitrite and algae Amphora coffeaeformis .